A Retrospective Study of Lenvatinib Monotherapy or Combined With Programmed Cell Death Protein 1 Antibody in the Treatment of Patients With Hepatocellular Carcinoma or Intrahepatic Cholangiocarcinoma in China - Zhu, Sihui; Liu, Chenxi; Dong, Yanbing; Shao, Jie; Liu, Baorui; Shen, Jie (Frontiers in Oncology, 2021)
Lenvatinib has been ratified as a first-line medication for advanced liver tumors by the American Food and Drug Administration. To assess the effectiveness and security of Lenvatinib in the Chinese population in a real-world setting, we enrolled 48 patients with unresectable liver cancer, managed from December 2018 to March 2021. Among them, 9 and 39 (83.3% men) patients had intrahepatic cholangiocarcinoma (ICC) and hepatocellular carcinoma (HCC), respectively. Twenty-one (43.75%) patients had progressive disease after first-line treatment, and others (56.25%) had not receiving systemic treatment. Lenvatinib was administered alone or in combination with a programmed cell death protein 1 antibody (anti-PD-1). Treatment duration, median progression-free survival (mPFS), and median overall survival (mOS) were examined. The mOS and mPFS were 22.43 and 8.93 months, respectively. Of HCC patients treated with Lenvatinib only, the mOS and mPFS were 22.43 and 11.6 months, respectively. The corresponding values for HCC cases managed with anti-PD-1 combined with Lenvatinib were 21.77 and 7.1 months, respectively. ICC patients did not reach the mOS and their mPFS was 8.63 months. The present findings support the efficacy and security of Lenvatinib in the real-world therapy of Chinese patients with unresectable liver cancer.